Systematic Review: Paparan Karbon Monoksida Dan Gangguan Tekanan Darah Pada Dewasa Dan Lansia - Humaira Rofidah Zahra; Budiyono Budiyono; Nurjazuli Nurjazuli (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
The most common blood pressure disorders are high blood pressure and low blood pressure. One of the risk factors that is assumed to affect blood pressure is carbon monoxide exposure. This study aims to collect information about the association between carbon monoxide exposure and blood pressure disorders in adults and the elderly. Articles were collected through national journals database namely Portal Garuda and Google Scholar, and international journals through Pubmed, Scopus, and PROQUEST. The keyword combinations used are ‘karbon monoksida’, ‘tekanan darah’, ‘COHb’, ‘polusi udara’, ‘tekanan darah sistolik’, ‘tekanan darah diastolik’, ‘carbon monoxide’, ‘blood pressures’, ‘systolic blood pressure’, and ‘diastolic blood pressure’. The article search found out 20 articles eligible for inclusion criteria. The literature review shows the relationship between CO exposure and blood pressure. CO exposure can be at risk increased systolic blood pressure from 0.43 mmHg to 15 mmHg, as well as an increase in diastolic blood pressure from 0.39 mmHg to 9 mmHg. Acute or chronic carbon monoxide exposure has been shown to affect disorders on blood pressure characterized by an increase in both systolic and diastolic blood pressure.